2021
DOI: 10.1177/23259671211014230
|View full text |Cite
|
Sign up to set email alerts
|

Medial Ulnar Collateral Ligament Repair With Internal Brace Augmentation: Results in 40 Consecutive Patients

Abstract: Background: Medial ulnar collateral ligament (MUCL) repair has been proven to be effective in nonprofessional overhead-throwing athletes, with faster and higher rates of return to play (RTP) than the more traditional Tommy John reconstruction. Biomechanical studies and clinical data suggest that MUCL repair augmented with a collagen-coated internal brace may be an effective treatment option in this patient population. Purpose: To evaluate the functional outcomes of young nonprofessional athletes who underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Interestingly, only 3 videos discussed indications for UCL repair (as opposed to UCL reconstruction) despite an abundance of recent research demonstrating considerable success with UCL repair when performed for the proper indications. 15 , 35 , 47 , 48 This finding could be representative of the lag between the publication of novel research in peer-reviewed journals and the incorporation of these findings into freely available online video content. As orthopaedic surgery continues to evolve as a field, there will be a continued need to produce updated online patient education materials so that patients can fully consider all available options.…”
Section: Discussionmentioning
confidence: 78%
“…Interestingly, only 3 videos discussed indications for UCL repair (as opposed to UCL reconstruction) despite an abundance of recent research demonstrating considerable success with UCL repair when performed for the proper indications. 15 , 35 , 47 , 48 This finding could be representative of the lag between the publication of novel research in peer-reviewed journals and the incorporation of these findings into freely available online video content. As orthopaedic surgery continues to evolve as a field, there will be a continued need to produce updated online patient education materials so that patients can fully consider all available options.…”
Section: Discussionmentioning
confidence: 78%
“…Dugas et al 7 described a technique of repairing a torn UCL with suture tape (now called internal brace) augmentation. There have been other techniques described, 13 , 14 , 19 22 all with the same indications of acute UCL injury with good ligamentous quality. In a study by Rothermich et al 18 of Division 1 National Collegiate Athletic Association baseball players who underwent UCL surgery, the proportion of patients who underwent UCL repair increased each year, from 10% in 2017, to 20% in 2018, and 25% in 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Dugas et al 7 reported 5 complications from their cohort of 111 patients, with 3 related to either ulnar neuritis or instability, 1 due to heterotopic ossification, and 1 due to painful retained suture. A cohort of 40 nonprofessional overhead athletes with mean follow-up of 23.8 months were found to have a 92.5% return to play and mean Kerlan-Jobe Orthopaedic Clinic score of 92.6 after undergoing UCL repair by O’Connell et al 13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anterior bundle of the medial ulnar collateral ligament (MUCL) complex is the primary restraint to valgus stress at the elbow during overhead throwing. 32 , 36 Injury classically affects baseball pitchers, because of the high and repetitive stress on the ligament. 20 Primary repair was historically the treatment of choice.…”
mentioning
confidence: 99%